Post 2015: reconsidering sustainable development goals; is the environment merely a dimension? - Frederick Boltz; Will R. Turner; Frank Wugt Larsen; Imme Scholz; Alejandro Guarin (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
By the end of 2015, the United Nations will adopt a new global development agenda as a follow-up to the Millennium Development Goals (MDGs). To this end, UN member states are now engaged in a debate on defining universal Sustainable Development Goals (SDGs), as decided by the 2012 Rio+20 Summit. According to the final declaration of that summit, these goals should “address and incorporate in a balanced way all three dimensions of sustainable development and their interlinkages” and should “be coherent with and integrated into the United Nations development agenda beyond 2015” ( 246). This wording can be interpreted to mean that there is an agreed effort to build upon the MDGs in drafting the SDGs – that these are sequential and nested steps, not parallel processes, which will culminate in a global agenda for sustainable development by the end of 2015. But the SDGs have one key feature distinguishing them from the MDGs: they will be universal in nature, providing guidance for related domestic policies of all UN member states. This is an important departure from the MDGs, which set quantified and time-bound policy goals for developing countries, and included industrialised nations in a supporting role through development assistance. The SDG vision – with the potential to reduce barriers both among countries and among sectors – is a logical and needed step. Yet there are many political and institutional obstacles to ensuring an integrated set of goals: transitioning to SDGs will require a change of perspective by negotiators, who must bridge the gap between conventional approaches to economic development and poverty reduction on the one hand, and to environmental sustainability on the other. And it will require a whole-ofgovernment approach, instead of being the exclusive remit of ministries of environment and/or development cooperation. Several lines of thought favour an integrated set of goals. The idea that environmental concerns can be subordinated to economic growth disregards the fact that our society and economy are bound by a natural biophysical system that sustains life on earth. But human society and nature operate on different time scales: while solutions to human suffering are required now, environmental policies must address the long-term effects of today's economic actions. The welfare of people today is important, but the welfare of future generations matters too: their fates are intertwined. A universal set of SDGs can address the difficulties of global and intergenerational burden sharing. Negotiators should not shy away from the complexity this implies, as oversimplified goals will not be fit to the task at hand. The most challenging and important task will be to translate the adopted universal goals into quantified and timebound domestic goals at the country level. Rich countries will have to support developing countries in implementing domestic policies, while rising powers should volunteer to do so, too.
Keywords: 330; Aufstrebende Mächte; Deutsche + Europäische + multilaterale Entwicklungspolitik; Umwelt; Ökosysteme und Ressourcen